Rate of differentiation syndrome in patients based on timing of initial all-trans retinoic acid administration. (2019) - Nauffal, Mary; Werner, Lillian; Ni, Jian; Stone, Richard M.; DeAngelo, Daniel J.; McDonnell, Anne M.
Abstract: All-trans-retinoic acid (ATRA) is the standard of care for the management of acute promyelocytic leukemia (APL), but can be associated with differentiation syndrome (DS). Over a seven-year period, we sought to determine the impact of ATRA initiation time on the development of DS. ATRA administration time had no impact on DS occurrence ( p  = =0.13), APL risk ( p  = =0.28) or regimen received ( p  = =0.1). Patients with higher mean body mass index (BMI) were more likely to develop moderate or severe DS ( p  = =0.02). Early treatment of APL is essential and maybe strongly considered in patients with elevated BMI.